Meningkatkan Hasil Belajar Pakat Melalui Model Pbl Pada Peserta Didik Sd Negeri 6 Salaon Toba - Nurtina Pasaribu (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to improve the learning outcomes of Catholic Religious Education (PAKAT) through the application of the Problem-Based Learning (PBL) model among students at SD Negeri 6 Salaon Toba. The background of this research is the low learning outcomes of students in PAKAT, caused by the lack of active student engagement in the learning process and teaching methods that do not support the development of students' character competencies in line with Pancasila values. This study uses Classroom Action Research (CAR) conducted in two cycles at SD Negeri 6 Salaon Toba, with the research subjects being 14 Phase B Grade IV students, focusing on the topic